2020
DOI: 10.1136/bjsports-2019-101696
|View full text |Cite
|
Sign up to set email alerts
|

Female and male US Olympic athletes live 5 years longer than their general population counterparts: a study of 8124 former US Olympians

Abstract: ObjectiveTo quantify US female and male Olympic athletes’ longevity and the years of life lost or saved due to multiple causes of death as compared with the US general population.MethodsFormer US athletes who had participated in the summer or winter Olympic Games at least once between 1912 and 2012 were included. Olympians’ date of birth, death and the underlying causes of death were certified by the National Death Index. The Olympians’ overall and cause-specific mortality were compared with the US general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
1
24
0
3
Order By: Relevance
“…A previous study on the longevity of US Olympians revealed that the cohort benefited the average of 5 years of gain in life, mainly driven by the years saved from cancer and CVD deaths ( Antero et al, 2020 ). However, the study did not explore the potential survival advantage considering the isolated neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study on the longevity of US Olympians revealed that the cohort benefited the average of 5 years of gain in life, mainly driven by the years saved from cancer and CVD deaths ( Antero et al, 2020 ). However, the study did not explore the potential survival advantage considering the isolated neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection process follows the existing study on the longevity of the US Olympians ( Antero et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 ; 7 ; 9 ; 15 ; 28 ; 29 ; 36 ; 40 ; 41 ; 43 ; 44 ; 46 ; 53 ; 56 ; 57 ; 59 ; 60 ; 72 ; 75 ; 76 ; 83 ; 84 ; 87 ; 88 ; 90 ; 91 ; 92 ; 96 ; 118 ; 119 ; 121 ; 122 ; 129 ; 133 ; 136 ; 146 ; 147 ; 148 ; 149 ; 150 ; 152 ; 162 ; 163 ; 164 ; 165 ; 166 ; 167 ; 168 ; 169 ; 177 ; 181 ; 182 ; 183 ; 184 ; 196 ; 197 ; 206 ; 207 ; 208 ; 209 ; 211 ; 212 ; 218 ; 219 ; 220 ; 221 ; 222 ; 223 ; 224 ; 225 ; 235 ; 236 .…”
Section: Uncited Referencesunclassified
“…Tour de France cyclist live 6.3 years longer than the general French population, with neoplasms, not heart disease, being the chief cause of death 75 . Longevity findings are also seen in American Olympic athletes who show an additional 5.1 years and decreased rates of cardiovascular disease and cancer compared to regular Americans 76 . Greater LV mass (>220 g) has been associated with higher peak GXT SBP values in 24/51 male triathletes of similar trueV˙normalO2max (57.3 ± 7.5 vs 59.8 ± 9.5 mL/kg/min), age (37.2 years), and body weight participating in half‐ and full‐distance Ironman.…”
Section: Clinical Outcomes Of Exaggerated Blood Pressure Response In Athletesmentioning
confidence: 99%